SISTEM PENGHAWAAN PADA KAMAR HOTEL - Pandora Raharjo, Maria Carizza; Budi, Wahyu Setia; Prianto, Eddy (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Nowadays, development in urban areas is progressing very rapidly, accompanied by an increase in the number of residents and various kinds of activities carried out. Seeing this phenomenon, many developers are competing to build multi-layered high buildings. Air conditioning systems in high-rise buildings are generally carried out with artificial air arrangements. The Grand Edge Hotel Semarang building is one of the multi-layered high-rise buildings that will be the case study. This hotel building is located in Semarang on an area of 2860 m2, 7 floors above ground and 3 basement floors as deep as 9 meters from ground level, total floor area is 15,958 m2. The electricity used from PLN is 700 KVA, equipped with 1 generator unit with a capacity of 650 KVA. The ventilation system used in this building is in the form of an artificial air system, including: Direct Air Conditioning (AC) Fan Coil Unit with Split Ducting system, as many as 117 units, with capacities of 1.5 PK, 2 PK, 3.5 PK and 10 PK. The ventilation system used in terms of the specifications of the AC unit used is able to produce conditions according to the PERMENKES No. 1077/MENKES/PER/V/2011, especially in hotel rooms. The information obtained at this time is a prelude to obtaining quantitative-qualitative data about the existing problems, as well as the form of the solution, it is necessary to deepen and add cases in the project.Abstrak: Dewasa ini pembangunan di perkotaan melaju sangat pesat yang disertai dengan jumlah peningkatan penduduk dan berbagai macam aktivitas yang dilakukan nya. Melihat fenomena tersebut maka banyak dari para developer berlomba-lomba untuk membangun bangunan tinggi berlapis. Sistem penghawaan pada bangunan tinggi umum nya dilakukan dengan tatanan udara buatan. Bangunan Hotel Grand Edge Semarang adalah salah satu bangunan tinggi berlapis yang akan menjadi studi kasus ini. Bangunan hotel ini terletak di Semarang diatas lahan 2860 m2, berlantai 7 lapis diatas tanah dan 3 lantai basement sedalam 9 meter dari permukaan tanah, luas lantai total 15.958 m2. Tenaga listrik yang digunakan dari PLN sebesar 700 KVA, dilengkapi 1 unit genset dengan kapasitas 650 KVA. Sistem penghawaan yang digunakan bangunan ini berupa tatanan udara buatan, meliputi : Air Conditioning (AC) langsung Fan Coil Unit dengan sistem Split Ducting, sebanyak 119 buah, dengan kapasitas 1,5 PK, 2 PK, 3,5 PK dan 10 PK. Sistem penghawaan yang digunakan dari sisi spesifikasi unit AC yang dipakai mampu menghasilkan kondisi yang sesuai standar PERMENKES No. 1077/MENKES/PER/V/2011, khususnya pada kamar hotel. Â Info yang didapatkan saat ini adalah sebuah awalan untuk mendapatkan data kuantitatif-kualitatif tentang permasalahan yang ada, serta bentuk solusinya perlu diadakan pendalaman dan penambahan kasus di proyek.